1984
DOI: 10.1007/bf01311218
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of African swine fever virus antigenic proteins by immunoprecipitation

Abstract: African swine fever virus is a large, complex virion in which numerous proteins have been identified by biochemical techniques. Few of these proteins have been shown to react with antibodies from recovered swine, leading to speculation that the immunological unreactivity of some viral proteins might explain the inability of immune sera from surviving animals to neutralize the virus. We used immunoprecipitation of radiolabeled viral proteins to examine these sera in more detail. Gradient sodium dodecyl sulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…The molecular weights of the IP in this study (their corresponding number in kilodaltons) are similar to those reported by other laboratoi~es (1,7,14,21). Slight differences may be produced by the different molecular weight standard proteins taken as references, for example myosin which was taken as 220K (17) (17) to p 220 and p 150 (1,14), respectively.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The molecular weights of the IP in this study (their corresponding number in kilodaltons) are similar to those reported by other laboratoi~es (1,7,14,21). Slight differences may be produced by the different molecular weight standard proteins taken as references, for example myosin which was taken as 220K (17) (17) to p 220 and p 150 (1,14), respectively.…”
Section: Discussionsupporting
confidence: 84%
“…T h e e t e c t r o p h o r e t i c p a t t e r n o f p r o t e i n s in infected cells w a s similar in several cell t y p e s (MS, V E R O , B H K a n d pig l e u k o c y t e s ) a n d after infection with several virus strains (5), a l t h o u g h s o m e p r o t e i n s can c h a n g e in mobility (7). I n this work, viral s t r a i n 608 g r o w i n g in V E R O cells (608 V 55) s h o w e d a clear difference as c o m p a r e d to the 608 L 6, in t h a t the I P 10 d i s a p p e a r e d a n d a n e w p o l y p e p t i d e (IP 13.5) a p p e a r e d (Fig.…”
Section: Pattern Of Synthesis Of Viral Specific Polypeptides Ire Infementioning
confidence: 98%
“…Proteins larger than 150,000 molecular weight that have been found in intracellular ASF virus purified by sucrose sedimentation (44) were not detected in preparations of extracellular virus purified by Percoll sedimentation, but appeared as components of the vesicle fraction. The discrepancy between the number and the apparent molecular weights of the ASF virus protein bands described previously (6,27,44) and those described in this paper could arise from the degree of vesicle contamination in the purified virus fraction, the higher resolution of the electrophoresis system used here, and differences in the source of virus (strain, extra-or intracellular) and host cells.…”
Section: Discussioncontrasting
confidence: 66%
“…2a, b). Letchworth & Whyard (1984), by immunoprecipitation of infected cell proteins with hyperimmune pig serum, demonstrated the specificity of the reaction and identified 37 ASFV-induced polypeptides. In our case we have identified 33 polypeptides.…”
Section: Discussionmentioning
confidence: 99%